Performance of ESG Portfolios - Turtiainen, Ria (My University, 2019)
The growth of world’s population is continuously increasing hence, the demand for the natural sources expands along with. Simultaneously in many fields, development is obtained in which finance conducts a major role. Socially Responsible Investing (SRI) has been an interest of investors and research during the past decade. In addition of maximal returns the inventors postulate higher quality for the investments. Thus, the companies have been forced to invest in SRI matters. The most recent concept of responsible investing is ESG investing, representing Environment, Social and Governance issues. ESG ratings precisely examines the level of responsibility of companies by detailed and comprehensive method to provide an investor an accurate score of the level of responsibility. This thesis studies the level of performance of ESG portfolios. Study uses abnormal returns of S&P500 during 2008- 2018 and compares the level of performance when portfolios are formed in different percentage categories based on the ESG scores. Portfolio formation is constructed so the high and low ESG rated portfolios are separated into top and bottom 5%, 10%, 20% and 50% portfolios. The regression is made with using Carhart four-factor model. Ina addition, thesis examines how the financial crisis effects the ESG assets by adding GDP into the regression. Study follows the methodology of Kempf and Osthoff (2007). The regression does not report many significant results and R-squared is rather low in the outputs. Therefore, the methodology applied in ESG and the dataset of this study does not provide the expected outcome. Thesis concludes that a portfolio built of ESG rated assets does not overcome the market and the effect of financial crisis on excess returns is not significant. Likewise, there is no significant difference in excess returns between high and low ESG rated portfolios. This may be partly explained by the theory of investors learning.
Keywords: Responsible investing; ESG; SRI; return; risk; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|